Analyzing tourist expenditures incurred on long-, medium-, and short-haul trips to Taiwan - Wei-Tse Pai; Kieu-Thi Phan; Ca-Van Pham; Jie-Min Lee; Chi-Jung Hsieh (Annals of Tourism Research Empirical Insights, 2024)
This study examined the consumption demands of short-, medium-, and long-haul tourists in Taiwan, considering the effects of tourism attractiveness, generational cohorts, and nationalities on tourism consumption demand. We employed an Almost Ideal Demand System model to estimate the expenditures and price elasticities based on tourism expenditure data of 3018 visitors to Taiwan. The results indicated that varying degrees of price elasticity were observed among short-, medium-, and long-haul tourists. Long-haul tourists exhibited the highest elasticity in terms of shopping prices and expenditure. The factors influencing tourists' attraction to Taiwan were identified as the geographical convenience of their travel and their nationalities, which, in turn, affected their consumption demands. Thus, based on tourists' relevant characteristics to implement targeted marketing strategies.
Keywords: 330; Almost ideal demand system model; Generational cohorts; Nationalities; Price and expenditure elasticity; Tourism attractiveness; Travel distance